Analisis Literatur: Miskonsepsi pada Konsep Ikatan Kimia dan Implikasinya terhadap Pembelajaran IPA Dasar - Afridha Laili Alindra; Salma Nurhaliza Darmansyah; Nurhayati; Bagas Adisetyo; Mellisa Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Misconceptions about basic chemical concepts are still often found since science learning in elementary school because students have difficulty understanding abstract and submicroscopic concepts. This research aims to analyze the forms of misconceptions regarding chemical bonding material and their implications for science learning in elementary schools based on a literature review. The research uses a literature study method with data sources obtained from Google Scholar, SINTA, and Scopus. Data were analyzed using content analysis techniques through the stages of organizing, synthesizing, identifying, and drawing conclusions. The results of the study show that many misconceptions are found in the concepts of valence electrons, electron configurations, ionic bonds, covalent bonds, Lewis structures and particle representation. Difficulty understanding abstract concepts causes students to tend to build understanding based on concrete experience and simple reasoning. This pattern of misconceptions is also found in science learning in elementary schools so that it can influence understanding of chemistry at the next level. Therefore, science and chemistry learning needs to be designed more conceptually and based on visualization to help students build scientific understanding gradually since elementary education. Keywords: Misconceptions, Chemical Bonds Elementary School Science Learning; Abstract Concept;literature Review